If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3a = 2 Reorder the terms: 3a + x = 2 Solving 3a + x = 2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1x' to each side of the equation. 3a + x + -1x = 2 + -1x Combine like terms: x + -1x = 0 3a + 0 = 2 + -1x 3a = 2 + -1x Divide each side by '3'. a = 0.6666666667 + -0.3333333333x Simplifying a = 0.6666666667 + -0.3333333333x
| 8q=264 | | 6x^2+78x+216=0 | | 3(6+5y)=2(5+4y) | | 5(-2x-10)+2=-128 | | 3x-2(4-5x)=5-3x | | -3(x-1)=-3x-2 | | -0.25x-2=-6 | | 6xy+3xy+6xy+10xy=989 | | 5x^2-34=x | | -0.5x+5=0 | | 5a-a-2a= | | 6xy+3xy+6xy+10xy= | | 3[5+2(9-8)]= | | 12x-2=24x+2 | | 2x*2+2x*x+1x+2= | | 0.25x+10x-2=121 | | 4x+32=8x | | 5+.75x=-7 | | x^3+x^2+2x-3=0 | | 0.5x-5x+8=-28 | | 2-3+8= | | 7y+13=13y+7 | | -7-15=8 | | 2x+60=2x^2 | | 4n=6*1 | | (x/4)+6=13 | | 6d-3d+2d= | | 2ax+1=ax+5 | | 2x+4x-7=17 | | 8x-5=0 | | 5n+6=4 | | Xt-5=k |